Cybersecurity in Higher Education: Challenges and Measures for Information Storage - Elena Angelova (Bulgarian Journal of International Economics and Politics)
In the modern digital age, cyber security has emerged as an issue of extreme importance, impacting various sectors and industries worldwide. Notably, higher education institutions have become prime targets for cyber-attacks and other security breaches due to their possession of a vast array of valuable and sensitive information. These institutions store a wealth of personal, financial and research data, making them attractive to malicious actors seeking to exploit vulnerabilities in their information systems. The consequences of such threats can be severe, including reputational damage, financial loss and even legal consequences. Additionally, the disruptive nature of these attacks could significantly disrupt the academic and administrative operations of these institutions, adversely affecting students, faculty and staff. The purpose of this paper is to undertake a comprehensive examination of the issue of cyber security in higher education and to propose practical solutions to address these challenges. This review will look at the different types of cyber threats these institutions face, with a particular focus on identifying the associated problems and presenting effective solutions. It is imperative that higher education institutions should undertake proactive measures to address these concerns as this will protect their position, strengthen the confidence of their stakeholders and ensure the continued pursuit of their educational goals.